2010
DOI: 10.1089/pho.2009.2675
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Light (λ400–2000 nm) on Third-Degree Burns in Diabetic Rats: Immunohistochemical Study

Abstract: Our results suggest that the use of polarized light at 20 J/cm(2) effectively improves the healing of third-degree burns on diabetic animals at both early and late stages of repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Instrument heated until red and incandescent (11. 1%) [24,25] immersion in water at 95 °C (5.5%) [15], immersion in water at 100 °C (5.5%) [23], or cylindrical brass rod cooled to 77 K (5.5%) [21]. These find-ings suggested a good standardization between the experi-mental models of third-degree burns, allowing the reproduc-ibility of the experimental models (Table 1).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Instrument heated until red and incandescent (11. 1%) [24,25] immersion in water at 95 °C (5.5%) [15], immersion in water at 100 °C (5.5%) [23], or cylindrical brass rod cooled to 77 K (5.5%) [21]. These find-ings suggested a good standardization between the experi-mental models of third-degree burns, allowing the reproduc-ibility of the experimental models (Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…Of these, 1164 were excluded for not meeting the inclusion criteria of this systematic review: repeated study (n = 5), in vitro study (n = 120), clinical study (n = 62), systematic review (n = 76), ab-stract only (n = 47), it is not of third-degree burn (n = 854). Finally, 17 studies [4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] in which diverse treatment pa-rameters of injuries were assessed were included for critical evaluation of the effectiveness of PBMT in third-degree burn. The 17 selected studies totaled a sample of 845 animals and showed some common characteristics, namely the use of adult male Wistar rat with a mean weight of 278.5 g as an experimental model and the dorsal region of the animals as the region where burns were performed in all (100%) studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the vascular response is very important in diabetic wound healing, as vascular diseases are a common complication in patients with uncontrolled diabetes and that that causes delay in the repair process. 28 Oliveira et al 29 showed, in the recent study, the effectiveness of PL with the low dose (10.2 J/cm 2 ) in improving the healing of third-degree burns in diabetic animals at both early (mainly on the angiogenesis) and late (mainly on re-epithelialization of repair) stages. 29 Meireles et al 17 have also confirmed the positive effect of the use of phototherapy on the healing of burns.…”
mentioning
confidence: 99%
“…28 Oliveira et al 29 showed, in the recent study, the effectiveness of PL with the low dose (10.2 J/cm 2 ) in improving the healing of third-degree burns in diabetic animals at both early (mainly on the angiogenesis) and late (mainly on re-epithelialization of repair) stages. 29 Meireles et al 17 have also confirmed the positive effect of the use of phototherapy on the healing of burns. However, the positive effect was found with the use of a laser device, which is very costly when compared to PL devices.…”
mentioning
confidence: 99%